WORDS THAT TEACH: A SPEECH ACT ANALYSIS OF TEACHER -STUDENT DIALOGUES IN DANGEROUS MINDS (1995) - Andi Muh. Abrar Mattangkilang; Sukardi Weda; Harnita Rosalia (State University of Makassar, 2026)
This study focus on the dialogues between teachers and students in the movie